Behavioral and cognitive outcomes for clinical trials in children with neurofibromatosis type 1. (12th January 2016) - van der Vaart, Thijs; Rietman, André B.; Plasschaert, Ellen; Legius, Eric; Elgersma, Ype; Moll, Henriëtte A.
Abstract : Objective: To evaluate the appropriateness of cognitive and behavioral outcome measures in clinical trials in neurofibromatosis type 1 (NF1) by analyzing the degree of deficits compared to reference groups, test-retest reliability, and how scores correlate between outcome measures. Methods: Data were analyzed from the Simvastatin for cognitive deficits and behavioral problems in patients with neurofibromatosis type 1 (NF1-SIMCODA) trial, a randomized placebo-controlled trial of simvastatin for cognitive deficits and behavioral problems in children with NF1. Outcome measures were compared with age-specific reference groups to identify domains of dysfunction. Pearson r was computed for before and after measurements within the placebo group to assess test-retest reliability. Principal component analysis was used to identify the internal structure in the outcome data. Results: Strongest mean score deviations from the reference groups were observed for full-scale intelligence (−1.1 SD), Rey Complex Figure Test delayed recall (−2.0 SD), attention problems (−1.2 SD), and social problems (−1.1 SD). Long-term test-retest reliability were excellent for Wechsler scales ( r > 0.88), but poor to moderate for other neuropsychological tests ( r range 0.52–0.81) and Child Behavioral Checklist subscales ( r range 0.40–0.79). The correlation structure revealed 2 strong components in the outcome measures behavior and cognition, with no correlation between these components. Scores on psychosocial quality of life correlate strongly with behavioral problems and less with cognitive deficits. Conclusions: Children with NF1 show distinct deficits in multiple domains. Many outcome measures showed weak test-retest correlations over the 1-year trial period. Cognitive and behavioral outcomes are complementary. This analysis demonstrates the need to include reliable outcome measures on a variety of cognitive and behavioral domains in clinical trials for NF1.